Pengembangan E-Book Interaktif untuk Meningkatkan Kemampuan Menulis Paragraf Argumentasi Kelas IV - Agnesti Bilqis; Prana Dwija Iswara; Ani Nur Aeni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The goal of using interactive e-books as learning tools is to help teachers and students write persuasive paragraphs. In the arduous task of writing argumentative paragraphs, students continue to battle to persuade the reader, and the built-in sentences remain difficult to understand. Interactive e-book media feature aspects of argumentative paragraphs such as definitions, traits, examples, and practice. This study evaluates the viability of e-book products designed for fourth-grade elementary school students using the three-step Research and Design (R&D) method: planning, design, and development. On several devices, students can view interactive e-book media made with the application Canva. The researcher validated the product's content, media, and trials with the intended audience (students) to determine the product's viability. The validation of the content yielded a score of 63 out of a maximum of 65, suggesting that 97% of the material was legitimate. The media validity percentage was 91%, with a score of 41 out of 45 for the media validation results. The validity rate of student trials was 85%. This medium is engaging for children and has the potential for repeated use in writing training. The findings of this study suggest that educators should create media to enhance learning.